If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 40 = 15x + 100 Reorder the terms: 40 + 5x = 15x + 100 Reorder the terms: 40 + 5x = 100 + 15x Solving 40 + 5x = 100 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 40 + 5x + -15x = 100 + 15x + -15x Combine like terms: 5x + -15x = -10x 40 + -10x = 100 + 15x + -15x Combine like terms: 15x + -15x = 0 40 + -10x = 100 + 0 40 + -10x = 100 Add '-40' to each side of the equation. 40 + -40 + -10x = 100 + -40 Combine like terms: 40 + -40 = 0 0 + -10x = 100 + -40 -10x = 100 + -40 Combine like terms: 100 + -40 = 60 -10x = 60 Divide each side by '-10'. x = -6 Simplifying x = -6
| 2(2n+5)=18 | | 9-6c=-5c | | 63^2/6 | | 294/420=511/w | | 5y-7-2y=0 | | -9+9y=10y | | 35/y=65/39 | | 9z=6+3z | | 12x-12=6x+32+2x | | 6/7×=9/14 | | 8x+17=49 | | 4x+5x-2x+x= | | 28-u=258 | | -4n-6n+9=9 | | 2y^3-32y^2-450y=0 | | 6/s=15/17.5 | | 6(6-3)-3= | | -14m-11=85 | | 2/3m-2=10 | | 2x=x-2+54 | | 975/195=p/1 | | (2y+8x)= | | -8(1+4x)-168= | | 48/96=g/6 | | 8+4=-4 | | 17-19=-2x | | (x-2)(x+3+3i)(x+3-3i)=0 | | 2y^3-10y^2-72y=0 | | 531/v=675/750 | | 9x-20=26x+30 | | 4y-18+y+14= | | 12Y=99 |